The effects of GenAI on learning performance: A meta-analysis study - Gokoglu, Seyfullah; Erdogdu, Fatih (Educational Technology ＆ Society, 2025)
Artificial Intelligence (AI) has become increasingly prevalent in education, and Generative AI (GenAI) has emerged as a new concept in AI technology. Educators continue to debate the advantages and disadvantages of GenAI in education. To guide these discussions, further analysis is needed to determine the impact of GenAI on educational outcomes. This study aims to investigate the effect of GenAI on learning performance using the meta-analysis method. This meta-analysis study synthesized the results of 31 articles involving 2646 participants. The results show that GenAI has a moderately positive effect on learning performance (g = .689). There is no publication bias in determining the validity of the effect. The analysis included the effect sizes of seven moderator variables: sample level, sample size, research design, learning domain, research setting, intervention duration, GenAI tool, and testing format. Only intervention duration, GenAI tool, and testing format significantly moderated the effectiveness of GenAI on learning performance.